Clavicular Bone Tunnel Malposition Leads to Early Failures in Coracoclavicular Ligament Reconstructions. (January 2013) - Cook, Jay B.; Shaha, James S.; Rowles, Douglas J.; Bottoni, Craig R.; Shaha, Steven H.; Tokish, John M.
Background: Modern techniques for the treatment of acromioclavicular (AC) joint dislocations have largely centered on free tendon graft reconstructions. Recent biomechanical studies have demonstrated that an anatomic reconstruction with 2 clavicular bone tunnels more closely matches the properties of native coracoclavicular (CC) ligaments than more traditional techniques. No study has analyzed tunnel position in regard to risk of early failure. Purpose: To evaluate the effect of clavicular tunnel position in CC ligament reconstruction as a risk of early failure. Study Design: Case series; Level of evidence, 4. Methods: A retrospective review was performed of a consecutive series of CC ligament reconstructions performed with 2 clavicular bone tunnels and a free tendon graft. The population was largely a young, active-duty military group of patients. Radiographs were analyzed for the maintenance of reduction and location of clavicular bone tunnels using a picture archiving and communication system. The distance from the lateral border of the clavicle to the center of each bone tunnel was divided by the total clavicular length to establish a ratio. Medical records were reviewed for operative details and functional outcome. Failure was defined as loss of intraoperative reduction. Results: The overall failure rate was 28.6% (8/28) at an average of 7.4 weeks postoperatively. Comparison of bone tunnel position showed that medialized bone tunnels were a significant predictor for early loss of reduction for the conoid (a ratio of 0.292 vs 0.248; P = .012) and trapezoid bone tunnels (a ratio of 0.171 vs 0.128; P = .004); this correlated to an average of 7 to 9 mm more medial in the reconstructions that failed. Reconstructions performed with a conoid ratio of ≥0.30 were significantly more likely to fail (5/5, 100%) than were those performed lateral to a ratio of 0.30 (3/23, 13.0%) ( P < .01). There were no failures when the conoid ratio was <0.25 (0/10, 0%). Conoid tunnel placement was also statistically significant for predicting return to duty in our active-duty population. Conclusion: Medial tunnel placement is a significant factor in risk for early failures when performing anatomic CC ligament reconstructions. Preoperative templating is recommended to evaluate optimal placement of the clavicular bone tunnels. Placement of the conoid tunnel at 25% of the clavicular length from the lateral border of the clavicle is associated with a lower rate of lost reduction and a higher rate of return to military duty.